Learning to teach geography in the secondary school : a companion to school experience - Lambert, David ; Balderstone, David (Routledge/Falmer, 2020)
Learning to Teach Geography in the Secondary School provides intending and practising teachers of geography with the practical skills to design, teach and evaluate varied and exciting lessons. It also helps them to acquire a deeper understanding of geography's role, purpose and potential in secondary education. The book explores how teachers may use geography as a vehicle for preparing pupils for uncertain environmental, cultural, social and economic futures